Accessory proteins of the RAS-MAPK pathway: moving from the side line to the front line - Silke Pudewell (Nature Portfolio, 2021)
Pudewell et al. discuss and advance our understanding of accessory proteins, which are crucial for the RTK-RAS-MAPK signalling cascade. They consider the therapeutic potential of targeting such modulators as an alternative to targeting constituent components of the RTK-RAS-MAPK signalling cascade in the treatment of diseases such as cancer.